ANALISIS PENDAPATAN USAHATANI KAKAO DI DESA SIDOLE KECAMATAN AMPIBABO KABUPATEN PARIGI MOUTONG - Riani, Riani (AGROTEKBIS, 2015)
Research on the analysis of the income of farming next to the dial plan in the village of cocoa in Sidole subdistrict of Ampbabo regency of Parigi Moutong aim to wished how much big find out the income side grafting for cocoa farmers in the village of Sidole sub-district of Ampibabo regency of Parigi Moutong with used formula ? = TR - TC. Data collection was carried out in January-Maret 2014. The calculation result analysis revenue the cocoa farming connect side in the village of Toliba showed that the average reception in received by farmers respondents in one multiply season crop aqualto Rp 7.662.418 /2,10 ha, or Rp Rp 4.370.000 /1,00 ha, while the average total cost incurred during the year amounted to Rp 5.032.525 /2,10 ha, or Rp 2.597.070 /1,00 ha, so that the average farmer's income in one multiply season crop aqualto Rp 2.629.893 /2,10 ha,, or 1.772.930 /1,00 ha. Thereby, you can assume that the use of the cocoa to increase farmer income and in order to improve the welfare of society especially for farmers cocoa.